Correlation of Health Literacy with Quality of Life in Athletic Disabled Women - Anahita Khodabakhshi-koolaee; Mohammad Reza Flasafinejad; Zahra Mayeli Khezerloo; Farima Mohamadi (Hamadan University of Medical Sciences, 2018)
Background and Objectives: Due to its role in promoting appropriate decisions on the health of individuals, health literacy can affect their quality of life. This study aimed at determining the correlation between health literacy and quality of life in athletic disabled women in Tehran. Materials and Methods: This cross sectional descriptive study was conducted in 2017 among 169 athletic disabled women of the federation for the disabled and veterans in Tehran, who were selected by simple random sampling. Quality of life (SF-36) and health literacy questionnaires (HELIA) were used to collect the data. The data were analyzed by SPSS 20, using Pearson correlation coefficient and liner regression test. Results: The mean score of total health literacy was 101.29±28.79 and the mean score of total quality of life was 53.02±21.94. There was a direct and significant correlation between the dimensions of physical and mental health of quality of life with all aspects of health literacy (p<0.01). Also, availability, reading, comprehension, evaluation, decision-making and application explained the variance in quality of life by 42.7%, 41.6%, 40.9%, 36.2% and 19.4% (p<0.05). Conclusion: Having fair health literacy could improve the quality of life of athletic disabled women.